M
Maxim Vexler
Please help me understanding how this boolean expression was simplified
1. ab + ab' + a'b =
2. a(b+b') + a'b =
3. a*1 + a'b =
4. a + a'b + 0 =
5. a + a'b + aa' =
6. a + b(a + a') =
7. a + b*1 =
8. a + b
I did a truth table on both function [1] & [8], they produce the same
result so they are the same function, but I can't seem to understand
using what theorem / postulate can move from line 5 to 6 ?
Appreciate the help,
Maxim.
Example was taken from "Art Of Assembly (DOS-16bit), Chapter 02, Page 48"
1. ab + ab' + a'b =
2. a(b+b') + a'b =
3. a*1 + a'b =
4. a + a'b + 0 =
5. a + a'b + aa' =
6. a + b(a + a') =
7. a + b*1 =
8. a + b
I did a truth table on both function [1] & [8], they produce the same
result so they are the same function, but I can't seem to understand
using what theorem / postulate can move from line 5 to 6 ?
Appreciate the help,
Maxim.
Example was taken from "Art Of Assembly (DOS-16bit), Chapter 02, Page 48"